Synthesis and Characterization of Co(II), Ni(II) and Cu(II) Complexes with a Macrocyclic Ligand 5,7,12,14-Tetramethyldibenzo (b, i)-1,4,8,11-Tetraaza Cyclotetra Dec-2,4,6,9,11,13-Hexaene - Thakur, S.N.; Brat Singh, Shiv; Kumar, Sanjay (Asian Journal of Chemistry, 2010)
A series of complexes of the type MLB2 M = Co(II), Ni(II) and Cu(II), B = H2O, pyridine and α, β or γ-picolines have been synthesised with the macrocyclic ligand, H2L. Characterisation of the ligand as well as complexes has been done on the basis of elemental analysis, spectral studies, conductivity and magnetic susceptibility measurements. The ligand has been found to coordinate through all the four nitrogen atoms. The complexes are found to be octahedral. The remaining two coordination sites are satisfied by oxygen of H2O or nitrogen of nitrogen donor molecules such as pyridine and different picolines.